The relationship between multispectral satellite-derived vegetation indices and forage quantity and quality indicators in Mountain Zebra National Park - De Agrela, Robert Joao (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University, 2019.